Sunscreen Use, Awareness And Lifestyle Among Young Adult In Makassar - Andi Dinda Batari (Dinasti Research, 2024)
Sunscreens function as a barrier to block UV radiation. The harmful effects of UV can be prevented by using sunscreen and modifying lifestyle. The aim of this study is to find a correlation between sunscreen use, sunscreen awareness, and lifestyle in young adults. The study was an observational analysis with a cross-sectional design and was conducted in Makassar, Indonesia. Participants were young adults aged 18 to 35 years old and willing to fill out questionnaires. The data were analyzed with the Spearman test. There were 85 participants, they were 23.9 years old on average (SD = 3.99), female (83.5%), college students (52.9%), and employees (35.3%). Participants mostly answer very often for sunscreen use (43.5%). There was a correlation between sunscreen use and factors such as awareness due to benefits (p < 0.001), preventive objectives (p < 0.001), activity (p < 0.001), and finances (p = 0.048). A correlation was found between the use of sunscreen and drinking enough water (p = 0.031). In general, lifestyle is not yet healthy, but sunscreen use and drinking enough water showed sufficient awareness of improving health.